Hemodiálise intermitente em cães com doença renal crônica III - Melchert, Alessandra [UNESP] (2017)
Intermittent hemodialysis (IHD) is a form of renal replacement that is used in veterinary medicine for cases involving drug removal, electrolyte imbalance, acute kidney injury, and chronic kidney disease (CKD). The aim of the present study was to verify the efficacy of IHD in dogs with CKD staged at grade III and to evaluate the effect of IHD on quality of life. Twelve dogs with CKD at stage III met the inclusion criteria and were divided equally into two groups. The control group (n=6) received only clinical treatment and intravenous fluid therapy, and the hemodialysis group (n=6) received clinical and IHD treatments. Blood samples were collected before and after treatments in both groups. We evaluated complications and clinical parameters of IHD every 30 minutes. Hemodialysis decreased serum urea, creatinine, and phosphorus. Despite the evident removal of nitrogen compounds, dialysis treatment did not increase survival time in these patients. The results of this study do not support the early use of dialysis in dogs with chronic kidney disease stage III.